Simulated optical absorption enhancement in random silicon nanohole structure for solar cell application - Hong, Lei (2014)
We have conducted a systematic simulation study on light absorption in a silicon nanohole structure that has randomness introduced into its structural parameters, which include the hole radius, depth, and position. It is found that light absorption is enhanced for the random structures compared to their periodic counterparts. This is attributed to additional resonances induced by the structural disorders, broadening of the existing resonance, and lower optical reflection. The highest light absorption is obtained for the structure with randomness in hole position, which achieves a 12.7% enhancement compared with the periodic structure.